VALIDITAS SUTRA DALAM PEMODELAN SEBARAN KONDUKTIVITAS LISTRIK AIR TANAH ALIRAN TUNAK YANG TERKONTAMINASI LIMBAH - Wayan Sudiarsa, I
Abstract: The purpose of this research is to examine the validity of SUTRA for electrical conductivity distribution modeling of steady flow ground-water contaminated by waste. The soil in the physic model is injected by a constant velocity of waste. The electrical conductivity of the ground-water from each node is measured using conductivitymetre. The results of the physical model and SUTRA\'s calculation are plotted with Surfer and both of them are compared. The conclusion is that SUTRA is valid for electrical conductivity distribution modeling of steady flow ground-water contaminated by waste.